Higher mean arterial pressure increases risk of in-hospital mortality in aneurysmal subarachnoid hemorrhage - Ramadhania, Nadya Noor; Darmawan, Ahmad Faisal; Sani, Achmad Firdaus (Faculty of Medicine, Universitas Trisakti, 2020)
Background The majority (80%) of spontaneous subarachnoid hemorrhage (SAH) cases are caused by cerebral aneurysm rupture. The reported case fatality rate of aneurysmal SAH is still as high as 25 to 50%. Even though studies on aneurysmal SAH have been conducted, the mechanism and factors contributing to its mortality have not yet been clearly understood. The present study aimed to determine the predictors of mortality in aneurysmal SAH.Methods This was an observational analytic cross-sectional study. Data of 264 patients with aneurysmal SAH was obtained retrospectively from the medical records. Age, degree of consciousness, blood pressure, absence of aneurysmal treatment and mortality were collected. The simple and multiple logistic regression were used to analyze the data.Results The in-hospital mortality rate of aneurysmal SAH was still very high, with 140 (53.1%) patients dying during hospitalization. Simple logic regression analysis showed that patients with older age, lower Glasgow Coma Scale (GCS) score, higher mean arterial pressure (MAP) and no aneurysm treatment had higher in-hospital mortality risk. However, multivariate logistic regression showed that the strongest in-hospital mortality predictor was higher MAP (aOR 2.29; p=0.025), while younger age (aOR 0.39; p=0.006) and aneurysm treatment (aOR 0.34; p=0.006) were independent protective factors against in-hospital death.Conclusion Patients with higher mean arterial pressure on initial measurement had higher risks of mortality. More endovascular neurointervention facilities are needed to decrease the mortality rate of aneurysmal SAH.